PENGARUH METODE PEMBELAJARAN LINGKARAN DALAM-LINGKARAN LUAR(INSIDE-OUTSIDE CIRCLE) TERHADAP HASIL BELAJAR EKONOMI - Narulita, Sari; Zainal, Vetri Yanti (Jurnal Elastisitas: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2019)
The use of learning methods that have not been properly used by teachers in the learning process in class is one of the causes of economic learning outcomes of many students who do not reach the value of the minimum completeness criteria set by the teacher. One method that can be used to improve student learning outcomes in teaching and learning is the inside-outside circle learning method. The purpose of this study was to determine the effect of the inside-outside circle learning method on the economic learning outcomes of students. This study uses an experimental method that is by using the inside-outside circle learning method. The population in this study were students of class X. IPS amounted to 58 students, where the sample consisted of class X. IPS 1 as an experimental class totaling 29 people and X. IPS 2 as a control class of 29 people. After testing the hypothesis on the similarity test of two averages and calculating the economic learning outcomes data using statistical formulas, then it can be thit = 6.37 and ttab = 2.00 at a significant level of 5% so that it is proven that hit> ttab .. With thus it can be concluded "There is an Effect of the Inside-Outside Circle Learning Method on the Economic Learning Outcomes of Class X Students,